Analisis Permintaan Terhadap Perilaku Konsumen Dan Produsen Dalam Islam Pada Masyarakat - Sindy Vebri Permatasari (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
Abstract : Consumer behavior is the behavior that consumers pay attention to in finding, buying, using, evaluating and ignoring products, services or ideas that are expected to satisfy consumers. Meanwhile the behavior of producers explains how the behavior of producers in producing products that always strives to achieve efficiency in their production activities. Writing scientific papers uses qualitative research methods and quantitative research. Qualitative research is research that uses data in the form of words, sentences, pictures, or data not in the form of interval and ratio scales but in the form of low scales, namely nominal and ordinal scales. Meanwhile, quantitative research is research that is more based on data that can be calculated to produce an interpretation. The results of this study are that consumer behavior in fulfilling their daily needs is based on several factors, such as income, motivation factors from within, satisfaction factors, and the price factor of an item itself. Meanwhile, those that affect the ups and downs of the quantity of supply are the price factors for other goods, the company's objectives, the cost of production factors, and the level of technology used in producing a good. Keywords : Consumer Behavior, Producer Behavior, Islam, Economics.